Experimental Evaluation of UWB Transmission Waveform with Body-Shadowing in an Indoor Environment - Supakorn Suwan; Sathaporn Promwong (My University, 2022)
Wireless radio transmission performance in a realistic environment is a significant issue for designing and evaluating in short-range transmission technologies. Human body-shadowing is a significant propagation effect in an indoor wireless communication network. This paper presents the measurement model of impulse radio transmission with human body-shadowing in an indoor environment with IEEE 802.15.4 multipath impulse parameters. The impulse radio transfer function measurement model for the human body impulse radio transfer function with frequency band cover from 3 GHz to 11 GHz. The optimum system evaluation of impulse radio transmission is due to the human body and antennas. The characteristics of impulse radio transmission loss are using decay factor, log-normal standard, clusters, and ray arrival rate. The contributions of this research can be evaluating the human body impulse radio transfer function. And the design of the wireless radio system with the body shadowing effects and ambient environments.
Keywords: Impulse response; Body area network; Radio spectrum; Ultra-Wideband Communications Technology